Microfluidic Devices for Studying the Effect of Netrin‐1 on Neutrophil and Breast Cancer Cell Migration. Issue 4 (12th March 2018) - Hipolito, Jolly; Peretz‐Soroka, Hagit; Torres, Aniel Moya; Booy, Evan; Yang, Ke; Gupta, Monika; Meier, Markus; McKenna, Sean; Koch, Manuel; Santos, Susy; Stetefeld, Jörg; Lin, Francis
Abstract: Netrin‐1 is well‐known for its chemoattractive and chemorepulsive properties for axon guidance. Early studies report that netrin‐1 inhibits granulocyte migration. On the other hand, netrin‐1 can promote cancer cell migration and invasion. The underlying mechanisms are not well understood, which requires more in‐depth characterizations of netrin‐1 mediated immune and cancer cell migration. The present study, for the first time, employs microfluidic devices that are recently developed to quantitatively investigate the effects of netrin‐1 on the motility and chemotaxis of human blood neutrophils and human breast cancer cells under well‐controlled gradient conditions. The results show that netrin‐1 reduces chemokinetic motility of human neutrophils, which is accompanied with reduced cell polarization and spreading. In addition, netrin‐1 reduces neutrophil chemotaxis to N‐formyl‐Met‐Leu‐Phe on fibronectin substrate but interestingly not on collagen substrate. By contrast, netrin‐1 promotes the migration of human breast cancer cells. Furthermore, it is found that netrin‐1 reduces neutrophil chemotaxis to the supernatant of human breast cancer cell culture. Collectively, this microfluidic cell migration study provides quantitative characterizations of the effects of netrin‐1 on the motility and chemotaxis of neutrophils and breast cancer cells, and further suggests the potential role of netrin‐1 in regulating neutrophil recruitment to breast cancer microenvironments. Abstract : Microfluidic devices are employed to quantitatively investigate the effects of netrin‐1 on the migration of neutrophils and breast cancer cells. The results show that netrin‐1 significantly affects motility and chemotaxis of neutrophils in a substrate‐dependent manner and promotes the migration of breast cancer cells. Furthermore, the results reveal the role of netrin‐1 in regulating neutrophil recruitment to breast cancer microenvironments.